Dashboard information model for social research network sites - Siti Hawa, Apandi (2016)
The Social Research Network Sites (SRNS) is an online platform used by researchers for research related activities. Due to huge amounts of information in the current SRNS, sometimes this information overwhelms the researchers. A research-related dashboard information model is proposed to minimize the information overflow in the SRNS and it provides awareness on research-related information. The analysis on the relevance of having a dashboard has been done, and the results shows that it is a significant tool in assisting the researcher needs on monitoring their own research performance, monitoring research trends and alerting them with upcoming events. The proposed dashboard items that are possible to be included in the dashboard information model are identified based on analysis from literature studies and by review on the current SRNS. A survey was conducted in order to validate the dashboard items. Based on the result of factor analysis, the dashboard items can be grouped into three which are publication impact, publication achievements and alert on upcoming events. From the three group of the dashboard items, the dashboard information model is developed that has three dashboard components which are researcher performance (M1), impact of researcher publication (M2) and research events alert (M3). Then, we design a mock-up prototyping which represent the dashboard information model. The mock-up prototyping has been used for the dashboard information model verification purpose through interview with selected researchers. The result from the interview has shown that the researchers accepted and intended to use the mock-up prototyping that representing the dashboard information model. A few suggestions for enhancement of the dashboard items to be included in the dashboard information model have been received from the feedbacks. The dashboard information model that has been established is useful to be embedded in SRNS in order to aware the researchers on the research-related information. The embedded of the dashboard information model in the SRNS can attract more users to use the SRNS. The developers of SRNS can utilize the dashboard information model as a guideline in developing a better SRNS for the researchers.